Atrial Cardiomyopathy: a Role in the Pathogenesis of Atrial Fibrillation and Influence on the Results of Its Treatment - Oleksandr S. Stychynskyi; Pavlo O. Almiz; Alina V. Topchii (Ukrainian Journal of Cardiovascular Surgery, 2021)
The work is dedicated to the issue of atrial cardiomyopathies (ACs). They have a significant effect on the heart function, provoke rhythm disturbances and increase the risk of thromboembolic complications.The aim. To analyze the latest publications on the topic.The material for the analysis were the papers published by the leading arrhythmological clinics.Discussion. This paper describes the origin of the term “atrial cardiomyopathy”, highlights the conditional classification of changes in the atrial myocardium according to the EHRAS classification. The causes of this nosological form may be some types of gene mutations, as well as hypertension, congestive circulatory failure, diabetes mellitus, myocarditis, etc. ACs play an important role in the occurrence of atrial fibrillation (AF) and also affect its natural course and treatment outcomes. Electroanatomical mapping and magnetic resonance data show significant fibrotic changes in the atria in individuals with this form of arrhythmia. The DECAAF study (Delayed enhancement MRI and atrial fibrillation catheter ablation) showed that fibrotic changes in the atrial myocardium are directly related to the frequency of recurrent arrhythmias after catheter ablation. The DECAAFII study confirmed the effectiveness of the influence on the fibrous substrate in the catheter treatment of AF at stages 1 and 2 of fibrosis. The results of catheter treatment depend on the severity of fibrosis, which shows the importance of taking this factor into account when determining the indications for ablation.Conclusions. Thus, AC is an important component of the pathogenesis of AF. Improvement of techniques for influencing the fibrous substrate will improve the results of catheter treatment of AF.